2020
DOI: 10.32664/smatika.v10i02.450
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Tingkat Penerimaan E-Learning Sebagai Alternatif Media Pembelajaran Pada Siswa SMK

Abstract: E-learning adalah sebuah sistem pembelajaran yang menggunakan internet untuk proses belajarnya. Dalam kegiatan belajar, e-learning telah digunakan. Penelitian ini bertujuan untuk mengetahui dengan pasti tentang penggunaan e-learning yang digunakan sebagai media pembelajaran alternatif selain modul, khususnya bagi siswa SMK di Kota Malang. Maka penelitian ini dirancang dengan model penerimaan teknologi (TAM) dengan metode survey. Populasi dari penelitian ini adalah seluruh siswa SMK di Kota Malang pada tahun aj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Although the material can be accessed online, but with a lack of interaction and no guidance from the teacher, making the level of understanding of students low. There are complexities in the implementation of online learning (Amalia, Sulistyo, & Brata, 2020). This is in line with research from Putri (2015) states that low interaction between teachers and students will hinder the achievement of learning objectives.…”
Section: Discussionmentioning
confidence: 71%
“…Although the material can be accessed online, but with a lack of interaction and no guidance from the teacher, making the level of understanding of students low. There are complexities in the implementation of online learning (Amalia, Sulistyo, & Brata, 2020). This is in line with research from Putri (2015) states that low interaction between teachers and students will hinder the achievement of learning objectives.…”
Section: Discussionmentioning
confidence: 71%
“…Based on these findings, it can be concluded that changes do not influence user 112 Jurnal Infotel Vol. 13 No.3 August 2021 https://doi.org/10.20895/infotel.v13i3.662 trust in the e-learning system. This is because the features or technology available in the e-learning system are standard for students, and they already feel comfortable using it.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Covid-19 pandemic situation since March 2020 led UBL to 105 Jurnal Infotel Vol. 13 No. 3 August 2021 https://doi.org/10.20895/infotel.v13i3.662 issue a complete online learning policy in the second semester of the 2019/2020 academic year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internet has developed very rapidly to date in influencing media and communication. One of the factors supporting the success of the Internet in Indonesia is that infrastructure development has reached remote areas in Indonesia [1]. This can be proven by the increasing use of social media.…”
Section: Introductionmentioning
confidence: 99%